Policy-linkage for children with hearing disabilities; Perceptions from Basque Country in Spain and Chile. - Bustos Rubilar, Mario Andres; Junge Cerda, Patricia; Celedón Hidalgo, Natalia (Revista de Investigación en Logopedia, 2022)
Policy-Linkage and cross-sectoral work among health, education and social services has become relevant in early and biopsychosocial approaches in people with disabilities. In the context of children with hearing impairment, there would be controversies in this linkage due to discrepancies between clinical and sociocultural paradigms, concerning even the modalities of the language acquisition for this group. This qualitative study analyses semi-structured interviews seeking to describe the perceptions of different actors in the Basque Country of Spain and the Metropolitan Region of Chile. 565 minutes of interviews from 27 participants were analysed, from 3 emerging categories: existent polity and fields, policy-linkage among fields, and services delivered by each field. The results show a positive perception of policy-linkage and cross-sectoral work. Still, the preference of the biomedical model and clinical approach toward the disability over the biopsychosocial model and the development of the sociocultural approach persists.  This is prevalent whenever success is associated with typically development, through the acquisition of the spoken language rather than through diversity of other interventions. Perceptions of professionals from the areas studied differ around achievements considered as indicators of success.  A cross-sectoral policy and work coordinating centre, along with significant times from each area during the process could benefit the work towards the group.
Keywords: Public Policy; Deafness; Early Intervention